2021
DOI: 10.3390/ma14237350
|View full text |Cite
|
Sign up to set email alerts
|

Additively Manufactured Commercial Co-Cr Dental Alloys: Comparison of Microstructure and Mechanical Properties

Abstract: Laser-powder bed fusion (LPBF) is one of the preferred techniques for producing Co-Cr metal structures for dental prosthodontic appliances. However, there is generally insufficient information about material properties related to the production process and parameters. This study was conducted on samples produced from three different commercially available Co-Cr dental alloys produced on three different LPBF machines. Identically prepared samples were used for tensile, three-point bending, and toughness tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Metallic dental devices produced using LPBF of Co-Cr alloys show adequate yield strength, tensile strength and elongation as compared to cast Co-Cr alloys in a study which was conducted by Viderščak, Dalibor. et al [1]. It was reported by Viderščak, Dalibor.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Metallic dental devices produced using LPBF of Co-Cr alloys show adequate yield strength, tensile strength and elongation as compared to cast Co-Cr alloys in a study which was conducted by Viderščak, Dalibor. et al [1]. It was reported by Viderščak, Dalibor.…”
Section: Introductionmentioning
confidence: 90%
“…It was reported by Viderščak, Dalibor. et al [1] that the flaws typically found in cast Co-Cr alloys alloy were reduced in the samples that were processed using LPBF due to the homogeneity of the LPBF process. The mechanical properties of the Co-Cr samples processed using LPBF were found to be suitable for dental use according to the ISO 22674:2016 standard [2] and the tensile test data showed that the results achieved for a LPBF Co-Cr alloy are superior to that of a cast Co-Cr alloy Segbaya [3].…”
Section: Introductionmentioning
confidence: 99%
“…3 While there is data on the corrosion, microstructure, and osteointegration of additively manufactured Co Cr alloys, there is less on the fretting corrosion and wear properties. [4][5][6] This is especially true in relation to dental applications, since oral cavities feature varying situations influencing the tribocorrosion response of such alloys. 1 Additive manufacturing is growing in orthopedics in total joint arthroplasty for patient-specific implants and instrumentation, porous structures, as well as being applied in other novel applications.…”
Section: Introductionmentioning
confidence: 99%
“…PBF includes selective laser sintering (SLS), electron beam melting (EBM), and selective laser melting (SLM), with SLM being the most popular in dentistry 3 . While there is data on the corrosion, microstructure, and osteointegration of additively manufactured CoCr alloys, there is less on the fretting corrosion and wear properties 4–6 . This is especially true in relation to dental applications, since oral cavities feature varying situations influencing the tribocorrosion response of such alloys 1 …”
Section: Introductionmentioning
confidence: 99%
“…However, Co-Cr alloys are expensive, and the milling from disc technique has a low material efficiency for personalized parts, such as dental prostheses. That is why in recent years, additive manufacturing (AM) techniques have been studied as an alternative to traditional milling for Co-Cr alloys [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%